2000
DOI: 10.1161/01.cir.102.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Flow Velocity Is Related To Lumen Area and Regional Left Ventricular Mass

Abstract: Background-Coronary flow velocity varies widely between individuals, even at rest. Because of this variation, indices with less apparent deviation, such as the ratio of hyperemic to resting velocity (coronary flow reserve), have been more commonly studied. We tested the hypothesis that the flow continuity principle could be used to model resting coronary flow, and we examined the resulting velocity relationship. Methods and Results-We studied coronary velocity in 59 patients using a Doppler wire to measure res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
41
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 40 publications
7
41
1
1
Order By: Relevance
“…As Anderson et al demonstrated, the CFV is inversely related to the lumen size that exists for the distal myocardial bed; the decrease in basal CFV indicated the dilation of the coronary artery. 6 We observed this phenomenon both in echocardiographic and angiographic results in the present study. The basal CFV significantly decreased after NTG administration.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As Anderson et al demonstrated, the CFV is inversely related to the lumen size that exists for the distal myocardial bed; the decrease in basal CFV indicated the dilation of the coronary artery. 6 We observed this phenomenon both in echocardiographic and angiographic results in the present study. The basal CFV significantly decreased after NTG administration.…”
Section: Discussionsupporting
confidence: 75%
“…12 However, the present study significantly demonstrated the inverse relationship between flow parameters and LD in the patients, as previously shown in the animal study. 6 As NTG has been thought to dilate the larger coronary vessels and mostly have an impact on the epicardial artery, 13 the NTG-induced decrease of the baseline CFV suggested the significant dilatation of the epicardial arteries. While the baseline CFV varied, hyperemic CFV was relatively constant among the circumstances, before and after NTG administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mean coronary flow velocity is the same throughout the epicardial coronary system and thus the site where flow velocity is measured has no impact on the v-dp relation. 16 Some patients have aneurysmatic coronary arteries or a poststenotic dilatation. When flow was measured in a wide segment, flow velocities were lower and the v-dp relation became steeper, as demonstrated in figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial perfusion must be adequate to cope with increased myocardial oxygen demand, 25 but ventricular hypertrophy may potentially impair coronary blood flow. 26 Coronary reserve represents the ability of the heart to increase myocardial blood flow under circumstances of increased demand. Since wall tension may be represented by ventricular wall stress, coronary reserve/stress was devised as a surrogate of coronary flow/demand imbalance.…”
Section: Discussionmentioning
confidence: 99%